1976
DOI: 10.1139/b76-230
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxonomic studies in the Saxifragaceae s.l. 4. The flavonoids of Heuchera micrantha var. diversifolia

Abstract: 1976. Chemotaxonomic studies in the Saxifl-agaceae s.1. 4. The flavonoids of Herrc,I~c,lvi r?tic~rrrr~rl~tr var. c/i~~ersifu/iu. Can. J. Bot. 54: 21 33-2 140. Sixty flavonoids were isolated from aerial parts of Herrc~lrercr r?~icrcrrrrl~u var. cli~~c~rsifolio and identified. The flavonoid aglycones represented were kaempferol. quercetin. isorhamnetin, myricetin. laricytrin (myricetin-3'-0-methyl ether). syringetin (myricetin-3l.5'-di-0-methyl ether), and luteolin. Flavonol glycosylation patterns included 3-0-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

1982
1982
1988
1988

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(26 citation statements)
references
References 4 publications
0
26
0
Order By: Relevance
“…Earlier studies demonstrated that Tolmiea and Tellima possess different flavonoids (Collins and Bohm 1974;Collins et al 1975;Wilkins and Bohm 1976;Bohm 1979;Soltis and Bohm 1985). The two genera have similar arrays of kaempferol, quercetin, and myricetin 3-0-monoglycosides and 3-0-diglycosides (Table 2).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Earlier studies demonstrated that Tolmiea and Tellima possess different flavonoids (Collins and Bohm 1974;Collins et al 1975;Wilkins and Bohm 1976;Bohm 1979;Soltis and Bohm 1985). The two genera have similar arrays of kaempferol, quercetin, and myricetin 3-0-monoglycosides and 3-0-diglycosides (Table 2).…”
Section: Resultsmentioning
confidence: 97%
“…The methanol extract was subsequently treated following the procedures of Wilkins and Bohm (1976). Purified flavonoids were analyzed utilizing a combination of ultraviolet spectral methods (Mabry et al 1970), trifluoroacetic acid hydrolysis, and thin-layer chromatography against known compounds when available, following the methods of Wilkins and Bohm (1976). Sugar determinations also followed Wilkins and Bohm (1976).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in these ilies Pimceae (Niemann 1972(Niemann , 1977(Niemann , 1980Medvedeva et al. four species a limited amount of plant material was available 1974), Crassulaceae (Denton and Kerwin 1980), Saxifragsince myricetin occurs in the flowers only in trace amounts, it aceae (Wells and Bohm 1980;Wilkins and Bohm 1976), Resmight have k n undetectable to us. The occurrence of the tionaceae (Warborne et al 1985), Lirnnanthaceae (Parker and fourth aglycone, laricytrin, was strictly restricted to all species Bohm 1975), and Gingkoaceae (Geiger 1979).…”
Section: Resultsmentioning
confidence: 99%
“…The diglycoside and triglycoside fractions were fractionated similarly except that water-saturated ethyl acetate with increasing amounts of methylethyl ketone was used to resolve the diglycosides, and water-saturated methylethyl ketone was used to resolve the triglycoside fraction. Final purifications were accomplished by tlc and solvent systems described by Wilkins and Bohm (13). STRUCTURAL DETERMINATIONS.-FlaVOnOid structures were determined by standard methods of uv and pmr spectroscopy (14), partial and total hydrolysis using trifluoroacetic acid, and tlc against known compounds when available.…”
mentioning
confidence: 99%